Women's relational autonomy and the short story cycle: Olive Kitteridge by Elizabeth Strout. Issue 1 (1st April 2019) - Kadmos, Helena
Focussing on Elizabeth Strout's short story cycle, Olive Kitteridge (2008), this article proposes that contemporary collections of interconnected stories open new ways of understanding women's relational autonomy, and the importance of continuing relationships of interdependence and care. Here, relational autonomy is seen as a framework for shared beliefs that subjects' situated identities are formed within the context of social relationships and shaped by a complex intersection of social determinants, such as race, class, gender and ethnicity. This discussion proposes that the short story cycle is a particularly productive form for writers interested in exploring how women come to a greater sense of who they are through these relationships ‐ some enduring, others not ‐ as they are experienced through apparently mundane moments in women's lives. This is partly due to less emphasis on the individual trajectory of an autonomous person, and a greater focus on the shared experiences that shape identities and foster personal growth and collective fulfilment. The article seeks to explore this understanding of the cycle by reflecting on distinctive features of the form ‐ modular narrative structure and narrative openness ‐ seen in Olive Kitteridge, to demonstrate how this mode of storytelling helps make salient women's relational lives.